(untitled) (Research, Society and Development, 2020)
The study aimed to investigate how learning is assessed at the Federal Institute of Education, Science and Technology of Ceará (IFCE), Sobral Campus, comparing the Didactic Organization Regulation (ROD) with the teaching practice, and culminated with a pedagogical orientation action. It was motivated by an interest in understanding whether the assessment process may be affecting campus academic flow rates. The analysis and theoretical foundation were based on the five generations of evaluation (Lima Filho e Trompieri Filho, 2012) and Scriven’s formative assessment concept (Rios, 2006). Being an action research, the cycle followed in which the practice is improved by the systematic interchange between acting and investigating (Tripp, 2005). The qualitative methodology originated from the documentary analysis of the regulation and the application of questionnaires to the teachers. With this information, the pedagogical intervention was planned and performed to discuss the difficulties and guide the teachers in the practice of formative assessment. The results showed that the evaluation in the ROD / IFCE has a formative character and that 51% of the teachers are aligned with this conception. However, most still prioritize quantitative aspects and hold students accountable for difficulties in the process. The intervention stage was positively evaluated and proved the need to deepen this topic discussion with other training actions and complementary studies.